Biophysical controls over fire regime properties in Central Portugal - Bergonse, Rafaello (2021)
The concept of fire regime can be used to describe, with different degrees of complexity, the spatial and temporal patterns of fires and their effects within a given area and over a given period. In this work, we explore the relations between fire regime and a set of potential biophysical controls at a local scale, for 972 civil parishes in central Portugal. The fire regime was characterized with reference to a 44-year period (1975–2018) using three properties: cumulative percentage of parish area burned, area-weighted total number of wildfires, and the Gini concentration index of burned area over time. Potential control variables included topography, seasonal temperature and rainfall, and land use/land cover type and patch fragmentation. Ordinal logistic regression was used to model the relations between the fire regime properties and the potential control factors. Results show that the fire regime properties have important spatial contrasts within the study area, and that land use/land cover distribution, spring rainfall and summer temperatures are the major controls over their variability. The percentage of each parish occupied by shrubland and spontaneous herbaceous vegetation is the single most important factor influencing cumulative percentage of parish area burned and the Gini concentration index of burned area, whereas spring rainfall is the foremost factor regarding area-weighted total number of wildfires. Along with the role of spring rainfall in promoting fuel availability later in the year, our results highlight the importance of the speed of regrowth of shrubland and spontaneous herbaceous vegetation after burning, pointing out the need of tailoring fuel management strategies to the properties of each parish.